Association of Height and Arm Span in Young Healthy Subjects - Bajimaya, Mahesh Man; Mahotra, Narayan Bahadur; Shrestha, Lava; Pradhan, Sait; Gurung, Sanyukta (Nepal Journal of Health Sciences, 2022)
Introduction: Height is used to calculating body mass index and body surface area which are used to interpret renal function tests and pulmonary function tests. The maximum vertical measurement of a person is the standing height. Arm span is the measurement between the tip of the middle finger of the right and left hands. The exact standing height of patients with abnormalities of disproportionate growth, spine deformities, skeletal dysplasia, limb deformities, amputated limb, pain, weakness or paralysis cannot be measured. In these conditions, an arm span may be used to determine the height of a person. Objective: This study aims to determine the association of height and arm span among the medical students of Maharajgunj, Medical Campus, Nepal. Methods: A cross-sectional analytical study was conducted among medical students in the Clinical Physiology Department of Maharajgunj Medical Campus from November 2020 to October 2021. Non-probability, the convenience sampling method was adopted and a total of 110 participants were enrolled in the study including 55 males and 55 females. Pearson’s correlation coefficient was used to find the association between height and arm span. A simple linear regression test was also used to formulate the equations of height and arm span and data analysis was done using SPSS version 25. Results: A significant positive correlation was observed between height and arm span where the total participants had r-value=0.765(p=0.00), males had r-value=0.557(p =0.00) and female had r-value=0.778(p=0.00). Conclusions: A strong positive correlation was observed between height and arm span among the participants.